Korean Red Ginseng water extract arrests growth of xenografted lymphoma cells - Park, Jae Gwang (J Ginseng Res, 2016)
BACKGROUND: Although numerous studies of the anticancer activities of Korean Red Ginseng (KRG) have been performed, the therapeutic effect of KRG on leukemia has not been fully elucidated. In this study, we investigated the antileukemia activities of KRG and its cellular and molecular mechanisms. METHODS: An established leukemia tumor model induced by xenografted T cell lymphoma (RMA cells) was used to test the therapeutic activity of KRG water extract (KRG-WE). Direct cytotoxic activity of KRG-WE was confirmed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The immunomodulatory activities of KRG-WE were verified by immunohistochemistry, nitric oxide production assay. The inhibitory effect of KRG-WE on cell survival signaling was also examined. RESULTS: Orally administered KRG-WE reduced the sizes of tumor masses. Levels of apoptosis regulatory enzymes and cleaved forms of caspases-3 and -8 were increased by this extract. In addition, expression of matrix metalloproteinase-9, a metastasis regulatory enzyme, was decreased by KRG-WE treatment. The proportion of CD11c+ cells was remarkably increased in the KRG-treated group compared to the control group. However, KRG-WE did not show significant direct cytotoxicity against RMA cells. CONCLUSION: Our results strongly suggest that the KRG might have antileukemia activity through CD11c+ cell-mediated antitumor immunity.